2013
DOI: 10.1088/1674-1056/22/1/014702
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous and time-averaged flow structures around a blunt double-cone with or without supersonic film cooling visualized via nano-tracer planar laser scattering

Abstract: In a Mach 3.8 wind tunnel, both instantaneous and time-averaged flow structures of different scales around a blunt double-cone with or without supersonic film cooling were visualized via nano-tracer planar laser scattering (NPLS), which has a high spatiotemporal resolution. Three experimental cases with different injection mass flux rates were carried out. Many typical flow structures were clearly shown, such as shock waves, expansion fans, shear layers, mixing layers, and turbulent boundary layers. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…[25] It has been used to investigate the supersonic mixing layer, boundary layer, aerooptics, and so forth. [24][25][26][27][28][29][30][31] As shown in Fig. 3, the NPLS system is composed of a nanoparticle generator, a dual-cavity Nd:YAG laser, an interline transfer double-exposure CCD camera, a synchronizer, and a computer.…”
Section: Npls Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…[25] It has been used to investigate the supersonic mixing layer, boundary layer, aerooptics, and so forth. [24][25][26][27][28][29][30][31] As shown in Fig. 3, the NPLS system is composed of a nanoparticle generator, a dual-cavity Nd:YAG laser, an interline transfer double-exposure CCD camera, a synchronizer, and a computer.…”
Section: Npls Techniquementioning
confidence: 99%
“…Nano-tracer planar laser scattering (NPLS) is a new flow visualization technique for measuring the fine structures of a supersonic flow. [24] In the present work, the supersonic flow over a double elliptic surface is experimentally investigated using NPLS and PIV techniques. The rest of the paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al 15 and Gao et al 16 have gained the structure and the complex shock system of the transverse jet flow field by numerical simulation method, respectively. Zhu Yang-zhu et al 17,18 revealed the fine structure of the flow field of two-dimensional and three-dimensional, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu Yang-zhu et al 17,18 revealed the fine structure of the flow field of two-dimensional and three-dimensional, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…NPLS is a flow visualization technique [22] with a high temporal-spatial resolution and can reveal fine structures of supersonic flow. The NPLS technique has been successfully applied in the experimental investigation of boundary layers, [23] backward-facing steps, [24] finite cylinders, [25] blunt double-cones, [26] supersonic mixing layers, [27] and so forth.…”
mentioning
confidence: 99%